Legal Analysis of the Implementation of Doctors' Medical Services: (Study of the Decision of the Constitutional Court Number 82/PUU-XIII/2015 Which Revokes Article 11 (Paragraph 1 and Paragraph 2) That Medical Personnel Are Not Health Workers) - Batmanlusi, Karel (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2025)
The study conducted is a legal scrutiny concerning the provision of medical services by physicians, in accordance with the 2015 Constitutional Court ruling which invalidated the notion that medical staff are not considered healthcare professionals. The research methodology employed is normative law analysis. Information gathering is done primarily through library research. The research process comprises three main phases - preparation, fieldwork, and data analysis. Findings from this investigation suggest that clearly delineating job responsibilities for healthcare professionals can lead to the delivery of effective and high-quality healthcare services to the public. Because all health workers have service specialties in accordance with their profession. This is what is referred to as (the right man on the right place) so that it no longer generates counterproductive work behavior by medical personnel. As a recommendation, the formation of a legislation needs to pay attention to the hierarchy of laws and regulations so as not to cause erroneous legal interpretations, especially defining it using clear legal language so that it is easily understood and carried out by all citizens.